Ordovician klippen structures of the Sierra de Umango: New insights on Tectonic evolution of the Western Sierras Pampeanas, Argentina - Tieppo Meira, Vinicius (2012)
The basement rock of the Pampean flat-slab (Sierras Pampeanas) in the Central Andes was uplifted and rotated in the Cenozoic era. The Western Sierras Pampeanas are characterised by metaigneous rocks of Grenvillian Mesoproterozoic age and metasedimentary units metamorphosed in the Ordovician period. These rocks, known as the northern Cuyania composite terrane, were derived from Laurentia and accreted toward Western Gondwana during the Early Paleozoic. The Sierra de Umango is the westernmost range of the Western Sierras Pampeanas. This range is bounded by the Devonian sedimentary rocks of the Precordillera on the western side and Tertiary rocks from the Sierra de Maz and Sierra del Espinal on the eastern side and contains igneous and sedimentary rocks outcroppings from the Famatina System on the far eastern side. The Sierra de Umango evolved during a period of polyphase tectonic activity, including an Ordovician collisional event, a Devonian compressional deformation, Late Paleozoic and Mesozoic extensional faulting and sedimentation (Paganzo and Ischigualasto basins) and compressional deformation of the Andean foreland during the Cenozoic. A Nappe System and an important shear zone, La Puntilla - La Falda Shear Zone (PFSZ), characterise the Ordovician collisional event, which was related to the accretion of Cuyania Terrane to the proto-Andean margin of Gondwana. Three continuous deformational phases are recognised for this event: the D1 phase is distinguished by relics of S1 preserved as internal foliation within inter-kinematic staurolite porphyroblasts and likely represents the progressive metamorphic stage; the D2 phase exhibits P-T conditions close to the metamorphic peak that were recorded in an S2 transposition or a mylonitic foliation and determine the main structure of Umango; and the D3 phase is described as a set of tight to recumbent folds with S3 axial plane foliation, often related to thrust faults, indicating the retrogressive metamorphic stage. The Nappe System shows a top-to-the S/SW sense direction of movement, and the PFSZ served as a right lateral ramp in the exhumation process. This structural pattern is indicative of an oblique collision, with the Cuyania Terrane subducting under the proto-Andean margin of Gondwana in the NE direction. This continental subduction and exhumation lasted at least 30 million years, nearly the entire Ordovician period, and produced metamorphic conditions of upper amphibolite to-granulite facies in medium- to high-pressure regimes. At least two later events deformed the earlier structures: D4 and D5 deformational phases. The D4 deformational phase corresponds to upright folding, with wavelengths of approximately 10 km and a general N-S orientation. These folds modified the S2 surface in an approximately cylindrical manner and are associated with exposed, discrete shear zones in the Silurian Guandacolinos Granite. The cylindrical pattern and subhorizontal axis of the D4 folds indicates that the S2 surface was originally flat-lying. The D4 folds are responsible for preserving the basement unit Juchi Orthogneiss synformal klippen. This deformation corresponds to the Chanica Tectonic during the interval between the Devonian and Carboniferous periods. The D5 deformational phase comprehends cuspate-lobate shaped open plunging folds with E-W high-angle axes (D5 folds) and sub-vertical spaced cleavage. The D5 folds and related spaced cleavage deformed the previous structures and could be associated with uplifting during the Andean Cycle.